Burn out and teaching identity in a binational cultural center in Bogotá, Colombia : a mixed methods study (2020)
The present research study examined the relationship between teachers' wellbeing and their perceptions of their professional identity in a binational cultural center in Bogotá, Colombia. The study had three main objectives. First, to determine the rate of Burn Out Syndrome in the participants. Second, to determine the characteristics of teaching identity in the population, and third, to establish a possible relationship between the rates of Burn Out and the characteristics of teaching identity in the participants. Quantitative and qualitative data were analyzed separately first, and subsequently brought together to establish a possible relation between the constructs of the study. The findings showed that there is no evidence of Burn Out according to the official scales that measure the syndrome, however, the participants showed levels of emotional exhaustion and depersonalization. On the one hand, the findings demonstrated that the majority of the participants felt personally fulfilled, but the results also showed that they expressed levels of discomfort with different areas in their work and life. Such feeling are related to recognition, negative feelings towards the institution, frustration for not being able to accomplish personal, academic or professional goals, distress and critics to the methodology and assessment system in the center. In sum, the study concluded that though the participants feel personally and professionally fulfilled because of their labour as teachers and members of the institution, they also feel levels of exhaustion and depersonalization because of their workload and the requirements of the workplace. Most importantly, the study concluded that the categories that measure the Burn Out syndrome shape the participants' perceptions about professional identity and affect their self-image depending on the positive or negative experiences they have in their role as teachers